MYTHOPOETICS OF MELVILLE'S NOVEL "MOBY DICK" - Z. Eyyubova (Zenodo, 2023)
Abstract The main work of Herman Melville, the final work of the literature of American Romanticism. A long novel with numerous lyrical digressions, imbued with biblical imagery and multilayered symbolism, was not understood and accepted by contemporaries. The novel was written quickly. 760 pages took less than two years. So, in 1851, Moby Dick was published - a novel, or rather a poem, the American version of the Bronze Horseman, about the exorbitant pride of Captain Ahab, who planned to take revenge on the elements, and about the helpless wisdom of his assistant Starbuck, who decided to raise his hand against his distraught captain. The article analyzes H. Melville's novel "Moby Dick" in a mythological context. Changes in artistic ontology based on mythopoetics, contamination of the epic and the novel, and forms of identification of consciousness and space, human existence are taken into account. The change in the novel of reconciliation, and mythological thinking. The novel also analyzes the mytho-symbolism of things, sacrifice, initiation, carnival laughter and other issues. At the heart of this unique work is the pursuit of a white whale. An exciting plot, epic sea paintings, a description of vivid human characters in harmonious combination with philosophical generalizations make the book a masterpiece of world literature. References: 1. Aliyev R. Dastan strukturunda degenerativ zaman, "Dede Qorqud", 2021 N2, p. 21-33 2. Mehdi N. Senetin arxeologiyası. Senetin arxitektonikası. Bakı, Qanun neşriyyat, 2007, p.344 . 3. Melvill H. Mobi Dik, yaxud Aq Balina. – Bakı: Şerq-Qerb, 2011, p.608 . 4. Quliyev Q. XX esr Amerikan edebiyyatshunaslıqında aparıcı cereyanlar. – Bakı, 2011, p.208 . 5. Rzasoy S. "Dede Qorqud" eposu. I kitab. Qehramanın olub dirilmesi. Bakı, Elm ve tehsil, 2022, p.128 . 6. Freydenberg O.M. Poetika sujeta i janra.Moskva,Labirint.1997 p.448